The influence of rosella flower tea on blood pressure reduction in hypertension patients - Anggraini, Siska Sakti; Nur, Siti Aisyah; Morika, Honesty Diana; Sari Dewi, Ratna Indah (International Journal Of Community Medicine And Public Health, 2020)
Background: Hypertension is called the silent killer because it does not provide specific symptoms, it can increase the incidence of strokes, heart attacks, chronic kidney disease if not controlled and controlled properly. Management of hypertension is generally with pharmacological therapy that has not shown improvement. Non-pharmacological treatment using rosella flower tea which functions to open blood vessels wider, reduce blood viscosity and increase urine production so as to reduce blood volume. The purpose of this study was to study the effect of rosella tea on reducing blood pressure in hypertensive patients. Methods: This study uses a quasi-experiment design with the two-group pre-test and post-test design approach. This research was conducted on patients with hypertension at the Padang city health center with an intervention group of 16 respondents and a control of 16 respondents. Data analysis in this study used univariate and bivariate using independent t-test statistics. Results: The results of the study showed the average blood pressure in the systolic pretest intervention group 147.81 for 94.69 diastole and posttest systole 129.06 posttest diastole 78.75 while the control group for systole pretest 154.6 for diastole 96.25 and posttest without posttest treatment systole 129.06 postest diastole 78.75. Obtained a p value 0,000 statistical test for systole and a p value 0,000 diastole. Conclusions: There is an effect of rosella flower tea on reducing blood pressure in patients with hypertension at the Padang city health center.